Diet and Oxidative Stress: A Way Forward towards Prevention of Chronic Diseases - Jothi Marie Feula A; Saravanan M; Anandhalakshmi S; James Rajesh J (Disease and Health Research: New Insights Vol. 10, 2024)
Oxidative stress results from an imbalance between the production of reactive oxygen species (ROS) and the antioxidant defence mechanisms of a cell. It causes damage to the cellular environment. This forms the basic pathophysiology of most chronic diseases, including cardiovascular, neurodegenerative, and metabolic disorders. Dietary patterns significantly influence oxidative stress levels. Rich antioxidant diets are said to reduce ROS, whereas pro-oxidant diets promote oxidative damage. This chapter emphasises the complex relationship between diet and oxidative stress and looks at markers such as malondialdehyde (MDA) and ischemia-modified albumin (IMA), among others. It stipulates how rich-in-antioxidant foods, including fruits and vegetables, as well as other micronutrients such as selenium, zinc, and magnesium, exert antioxidant effects against oxidative stress, while pro-oxidant dietary components-those foods that are processed, have high saturated fats, as well as sugars-push oxidative stress and inflammation. It also emphasises how different diets, Mediterranean, vegetarian, and Western diets affect oxidative stress. Evidence even shows that plant-based and Mediterranean diets are associated with reduced oxidative stress, whereas the Western diet encourages its increasing prevalence. Furthermore, research has revealed that oxidative stress is regulated by gut microbiota through diet effects. By making use of diets rich in antioxidants and reducing pro-oxidant intake, oxidative stress could be significantly brought down, thus giving an avenue of preventive management over chronic diseases. This chapter shall provide outlines on the role of diet as a modifiable risk factor to bring down oxidative stress and its long-term health effects.